Security Analysis of Grr Rapid Response Network using COBIT 5 Framework - Riadi, Imam; Sunardi, Sunardi; Handoyo, Eko (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 10, No. 1 April 2019, 2019)
Connection from the Internet is required to always be maintained under any conditions, but not always connectivity will run smoothly, lots of crowds or problems that require connections do not run smoothly. Application of security systems to overcome all problems and difficulties, both technical and non-technical which can affect system performance . GRR Rapid Response is the answer to internet network security. GRR asks for a client-server model, agents installed on the machine (client) to be able to communicate with the Grr server to access and provide unique client IDs. After setting this active and running, the server can send a request to the client who collects information, and the client sends a response to the request. After Grr is made, it is necessary to do a system evaluation and evaluation. The COBIT 5 framework is a good standard for determining the level of maturity of network security. The maturity level obtained is 2.899 can be decided at an institutional maturity level defined. The level of support the institution has agreed to, supports and supports all activities related to network security.